Linfonodo pulmonar na paracoccidioidomicose aguda infantil (relato de um caso). - de Campos, E. P.; Bertoli, C. J.; Barbosa, K. S. (FapUNIFESP (SciELO), 1992)
The primary complex like Ghon was observed in a child's clinical roentgenographic study. C.S., white, male, 6 years old, was born in Curitiba (PR), Brazil and living in Guaratingueta (SP), Brazil, developed common cold, bimodal diary fever, chills, shake and sweats. Dyspnea, cough with general lymphadenopathy. Foot and right shoulder arthralgias. Six months ago visited a cave, equitation practice, dog and cat contacts and no transfusion, frontal sweats, fever (38.4 degrees C). T.A. was 8/6, tachycardia in generalized lymphadenopathy. Cardiopulmonary system was normal, mesogastric tumoral mass, hepatosplenomegaly and no ascites. Bone marrow with eosinophilia; nodule demonstrated presence of P. brasiliensis, hypoalbuminemia; hyperglobulinemia; anemia; leukocytosis with eosinophilia. Immunodiffusion with exoantigen 43 kd of P. brasiliensis was 1/32. Primary complex like Ghon was observed in interstitial pneumonia followed by mediastinal and mesogastric mass (35 to 40 days). Clavicular osteolytic lesions (45 to 60 days) appeared during paracoccidioidomycosis therapy. Recovery was observed 2 months after treatment of acute infantile paracoccidioidomycosis.
Pulmonary lymph node in acute juvenile paracoccidioidomycosis (a case report)
Keywords: cotrimoxazole; Trimethoprim Sulfamethoxazole Combination; acute disease; biopsy; case report; child; differential diagnosis; fever; human; isolation and purification; lung; lung mycosis; lymph node; male; microbiology; Paracoccidioides; pathology; remission; review; South American blastomycosis; Acute Disease; Biopsy; Case Report; Child; Diagnosis, Differential; English Abstract; Fever; Human; Lung; Lung Diseases, Fungal; Lymph Nodes; Male; Paracoccidioidomycosis; Remission Induction; Trimethoprim-Sulfamethoxazole Combination